KEWENANGAN PERADILAN NEGERI DI BIDANG PERBANKAN SYARIAH STUDI PASAL 55 UU NO. 21 TAHUN 2008 - Musataklima, Musataklima (Al-Mawarid Jurnal Hukum Islam, 2010)
Theoretically between one court to another court split on the basis of jurisdiction (court separation system based on jurisdictions), in Article 55 of the Act No. 21 of 2008 has caused the intersection of two judicial authority of religious courts and public justice in sharia banking dispute. Why is this happening. According to the author of one of the reasons is the assessment stems from mistrust to unpreparedness and religious courts in resolving disputes shariah banking. Judicially Article 55 of the Act No. 21 of 2008 does not contradict horizontally with Article 49 of the Act No. 3 of 2006 and vertically not consistent with the Constitution of 1945. Solutions to the authority of sharia banking dispute settlement is to the exclusion of common justice to the logic of "Sertificate Property Rights which came first can not be undone by a certificate of ownership that comes later for the same object", and with the logic of lex specialis derogat leg generalis.